Utilization of Shrimp Shell Waste as Nitrogen Source in N-Doped TiO₂ for Degradation of Polyethylene Microplastics - Nurhasni Nurhasni; Annisaul Izzah; Aisyah Rahma Dwitami; Yuza Ahmad Gumilang; Zilfa Zilfa; Diana Vanda Wellia (Jurnal Kimia Sains dan Aplikasi, 2025)
Microplastic pollution presents a significant challenge globally, posing serious threats to aquatic ecosystems. This study explores the photocatalytic degradation of microplastics in aqueous solutions by applying nitrogen-doped TiO2 (N-TiO2) nanoparticles under visible light. The N-TiO2 nanoparticles were synthesized via the solvothermal method, utilizing chitosan derived from shrimp shell waste as a nitrogen source. The photocatalytic efficacy of the N-TiO2 nanoparticles was assessed for degrading model polyethylene microplastics, illuminated by a 50-watt LED lamp. Characteristic peak shifts in the FTIR absorption spectrum, notably at 3429 cm-1 to lower wavenumbers, and diminished amide I absorption at 1621 cm-1, confirmed the successful extraction of chitosan from shrimp shell waste. The synthesized N-TiO2 nanoparticles were in the pure anatase phase, exhibited a reduced bandgap of 2.97 eV, and showed enhanced absorption in the visible light spectrum (λ=400 – 800 nm) compared to undoped TiO2. The incorporation of nitrogen into the TiO2 matrix was validated by vibration bands at approximately 1035 cm-1 and 535 cm-1, corresponding to the Ti—N and Ti—O—Ti bonds, respectively. Optimal results were attained with TiO2 nanoparticles doped with 50% nitrogen, achieving a degradation rate of approximately 30.45% of a 250 mg/L microplastic solution over 50 hours of visible light exposure—nearly six times more effective than undoped TiO2. This study highlights the sustainable use of shrimp shell waste as a nitrogen source for enhancing TiO2 nanoparticles, showcasing their potential for environmental remediation applications.